A Physical Workload Index to Evaluate a Safe Resident Handling Program for Nursing Home Personnel. (June 2014) - Kurowski, Alicia; Buchholz, Bryan; ,; Punnett, Laura
Objective: The aim of this study was to obtain a comprehensive analysis of the physical workload of clinical staff in long-term care facilities, before and after a safe resident handling program (SRHP). Background: Ergonomic exposures of health care workers include manual handling of patients and many non-neutral postures. A comprehensive assessment requires the integration of loads from these varied exposures into a single metric. Method: The Postures, Activities, Tools, and Handling observational protocol, customized for health care, was used for direct observations of ergonomic exposures in clinical jobs at 12 nursing homes before the SRHP and 3, 12, 24, and 36 months afterward. Average compressive forces on the spine were estimated for observed combinations of body postures and manual handling and then weighted by frequencies of observed time for the combination. These values were summed to obtain a biomechanical index for nursing assistants and nurses across observation periods. Results: The physical workload index (PWI) was much higher for nursing assistants than for nurses and decreased more after 3 years (−24% versus −2.5%). Specifically during resident handling, the PWI for nursing assistants decreased by 41% of baseline value. Conclusion: Spinal loading was higher for nursing assistants than for nurses in long-term care centers. Both job groups experienced reductions in physical loading from the SRHP, especially the nursing assistants and especially while resident handling. Application: The PWI facilitates a comprehensive investigation of physical loading from both manual handling and non-neutral postures. It can be used in any work setting to identify high-risk tasks and determine whether reductions in one exposure are offset by increases in another.